Resilience and coping in trauma spectrum symptoms prediction: A structural equation modeling approach. (April 2015) - Stratta, Paolo; Capanna, Cristina; Dell'Osso, Liliana; Carmassi, Claudia; Patriarca, Sara; Di Emidio, Gabriella; Riccardi, Ilaria; Collazzoni, Alberto; Rossi, Alessandro
Highlights: We posit resilience as a factor interacting with coping to protect from stress. We used a structural equation modeling approach to investigate this interaction. A better clinical profile can be obtained only when resilience factors intervene. Resilience is a key factor explaining relations among coping and stress symptoms. Abstract: Resilience is increasingly recognized as a relevant factor in shaping psychological response to natural disasters. Aim of the study is to examine in the context of a natural disaster the potential effects of resilience on the relation between coping and trauma spectrum symptoms, using structural equation modeling. A sample of 371 students who survived the earthquake in L'Aquila (Italy) were cross-sectionally evaluated using Resilience Scale for Adolescents, Brief Cope and Trauma and Loss Spectrum scale. The model shows a direct path of positive and emotional coping styles on resilience. Emotional coping shows also a direct impact on the outcome; positive and emotional coping results to be positively correlated as well as emotional and disengagement coping styles. Resilience directly affects the PTSD symptoms, partially mediating the impact of the coping styles. The model explains 30% of the variance in the outcome, i.e. the Post-Traumatic Stress Disorder (PTSD) symptoms, with very good fit indexes. Resilience operates as a protective factor from stress symptom development. It is likely that emotional and disengagement coping skills are rapidly involved after a traumatic exposure but when problem focused coping intervenes, resilience allows it to buffer the stressors or even guides toward a more successful outcome.